Controlled Drug Release from Nanoengineered Polysaccharides - Ilker S. Bayer (Pharmaceutics, 2023)
Polysaccharides are naturally occurring complex molecules with exceptional physicochemical properties and bioactivities. They originate from plant, animal, and microbial-based resources and processes and can be chemically modified. The biocompatibility and biodegradability of polysaccharides enable their increased use in nanoscale synthesis and engineering for drug encapsulation and release. This review focuses on sustained drug release studies from nanoscale polysaccharides in the fields of nanotechnology and biomedical sciences. Particular emphasis is placed on drug release kinetics and relevant mathematical models. An effective release model can be used to envision the behavior of specific nanoscale polysaccharide matrices and reduce impending experimental trial and error, saving time and resources. A robust model can also assist in translating from in vitro to in vivo experiments. The main aim of this review is to demonstrate that any study that establishes sustained release from nanoscale polysaccharide matrices should be accompanied by a detailed analysis of drug release kinetics by modeling since sustained release from polysaccharides not only involves diffusion and degradation but also surface erosion, complicated swelling dynamics, crosslinking, and drug-polymer interactions. As such, in the first part, we discuss the classification and role of polysaccharides in various applications and later elaborate on the specific pharmaceutical processes of polysaccharides in ionic gelling, stabilization, cross-linking, grafting, and encapsulation of drugs. We also document several drug release models applied to nanoscale hydrogels, nanofibers, and nanoparticles of polysaccharides and conclude that, at times, more than one model can accurately describe the sustained release profiles, indicating the existence of release mechanisms running in parallel. Finally, we conclude with the future opportunities and advanced applications of nanoengineered polysaccharides and their theranostic aptitudes for future clinical applications.